2009
DOI: 10.1007/s00464-009-0392-8
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic sympathectomy for palmar and axillary hyperhidrosis: four-year outcome and quality of life after bilateral 5-mm dual port approach

Abstract: Currently different effective surgical approaches for the treatment of hyperhidrosis with improvement rates of more than 80% are available. The quality of the intervention has to be evaluated by changes in quality of life and intensity of compensatory sweating. Thoracoscopic sympathectomy as performed in our institution offers results and complications comparable to previously published trials; however, because of single-lumen ventilation the management is much easier. Therefore, this technique offers an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
1
13
3
Order By: Relevance
“…The prognostic factors currently associated with worsening of QOL following thoracic sympathectomy to treat hyperhidrosis are surgical failure and severe compensatory hyperhidrosis [23,24]. In contrast, with clinical treatment, we did not observe any worsening of QOL.…”
Section: Discussioncontrasting
confidence: 44%
“…The prognostic factors currently associated with worsening of QOL following thoracic sympathectomy to treat hyperhidrosis are surgical failure and severe compensatory hyperhidrosis [23,24]. In contrast, with clinical treatment, we did not observe any worsening of QOL.…”
Section: Discussioncontrasting
confidence: 44%
“…One of most troublesome side effects of thoracic sympathectomy is compensatory sweating, which interferes with the patient's quality of life and causes patient dissatisfaction [9][10][11]. Chang et al demonstrated that the degree of patient satisfaction is significantly inversely related to the severity of compensatory sweating after sympathectomy, which supports our results [12].…”
Section: Discussionsupporting
confidence: 88%
“…The prognostic factors currently associated with worsening of QOL following thoracic sympathectomy to treat hyperhidrosis are surgical failure and severe compensatory hyperhidrosis. 26,27 On the other hand, with clinical treatment, we did not observe any worsening of QOL. In the worst cases, QOL remained unchanged.…”
Section: Discussionmentioning
confidence: 50%